Does physical education foster skill acquisition in novices from childhood to adolescence? - Gromeier, Michael; Schack, Thomas; Koester, Dirk (Advances in Social Sciences Research Journal, 2019)
The goal of this study was to examine age and gender-related differences in quantitative and qualitative throwing performances of novices across a lifespan six to 16 years of age. Quantitative and qualitative throwing performances of 110 participants were evaluated in a controlled setting. The overall throwing movement was also sub divided into five essential movement characteristics: trunk, forearm, humerus, stepping, and backswing actions (Halverson & Roberton, 1984).The participants had to throw as hard and accurate as possible aiming a target on the wall. Each trial was videotaped for qualitative data analysis which has been conducted by using a modified component approach. The present findings show that across the three age bands, novices stagnated on a low level of movement development. Also, gender differences in the development of the throwing movement characteristics were found for the age band childhood and in some features gender differences were sustained throughout the examined age bands until adolescence. Within the novices, higher performance values in favour of male were found during childhood for trunk, forearm, and backswing actions, and in the quantitative performance-measure. Within the pubescence, gender differences existed only for trunk action and within the adolescence only for backswing action. There were no progress in throwing movement characteristics between the various levels of motor development. Thus, no improvement of the throwing movement quality and accuracy (quantity) could be recognised, which is calling for improvements in physical education. Compared with athletes in the same age, in contrast a study by Gromeier, Koester, and Schack (2017) show that with increasing age, qualitative performance of male and female athletes improves and furthermore it can be seen that male and female athletes demonstrated similar movement patterns in the main function phase. That raises questions concerns issue of physical education.